Reliable, accessible and transferable method for the quantification of flavanols and procyanidins in foodstuffs and dietary supplements. Issue 1 (14th January 2020) - Bussy, Ugo; May, Brian R.; Olanrewaju, Yusuf; Hewitt, Gregory; Anderson, Nicholas; Crozier, Alan; Ottaviani, Javier I.; Kwik-Uribe, Catherine
Abstract : Liquid chromatography coupled with fluorescence detection for accurate and precise determination of cocoa flavanol monomers and procyanidins in cocoa-based products. Abstract : Flavanols and procyanidins are plant-derived bioactives that are receiving increasing attention because of their potential health benefits. Analytical tools that can accurately identify and reproducibly quantify these bioactives are critical to researchers for test material characterization, as well as to the food industry and regulators, notably for product labeling. However, the chemical complexity of procyanidins, and the absence of analytical standards have prevented the development of methods that could serve the needs of these different sectors. This report describes the development and validation of a reliable, accessible and transferable method for the quantification of flavanol monomers and procyanidins in cocoa-derived dietary supplements and foodstuffs. To accomplish this, flavanols and procyandins from cocoa, one of the most studied dietary sources of these compounds, were used as a model system. To overcome limitations related to the absence of analytical standards, a cocoa extract was thoroughly characterized for use as a calibrant. It was then used in the development and validation of a method based on reliable and accessible instrumentation, namely HPLC coupled with fluorescence detection. The resulting method permitted the quantification of flavanols and procyanidins in amounts ranging from 2 to 500 mg g −1, with high precision (%RSD 0.2 to 1.9%) and accuracy (100.7 to 102.9%). The method was successfully applied to assess the flavanol and procyanidin content of different cocoa-based commercial products. Furthermore, the high precision of the methods showed the feasibility of using principal component analysis of flavanol and procyanidin profiles to discriminate cocoa-derived products by origin and manufacturing processes. A feature that offers advantages in monitoring product authenticity/adulteration. Overall, these findings support the application of this method for the routine analysis of cocoa flavanols and procyandins.